1058 UNIQUE TREATMENT OF PAP INTOLERANCE DUE TO RETROGRADE LACRIMAL DUCT AIRFLOW LEAK. (12th April 2019) - Roberts, Edmond; Chakapurakal, Steven; Liendo, Cesar; Scuteri, Bryan; Chernyshev, Oleg
Abstract: INTRODUCTION: Retrograde lacrimal duct airflow during positive airway pressure therapy is a rare complication which can lead to discomfort for the patient and non-compliance with PAP therapy. Report of Case: Patient is a 68-year-old male with a history of atrial fibrillation status post electrical and chemical cardioversion therapy, obesity(BMI: 30.8), heart failure with preserved ejection fraction of 63% and central predominant sleep apnea with central sleep apnea index of 79/hr. CSA was refractory to CPAP and BiPAP, but responded to ASV. Patient started experiencing a blowing sensation in his left eye along with dryness that was eventually diagnosed as retrograde lacrimal duct airflow leak facilitated by the use of nasal and oronasal mask. We surmised that the degree of the retrograde lacrimal airflow regurgitation likely resulted from excessive pressures in the initial titration, and we advocated for a repeat titration study with trial of O2 therapy and/or lower ASV settings as a contingency plan. On the following sleep study, supplementary oxygen therapy alone was able to decrease CAI to 38/h without attenuating obstructive events. Subsequently, lower ASV Pressure settings with low flow oxygen successfully eliminated central and obstructive events with persistent lacrimal duct reflux. Trialing the new ASV pressure with a total face mask, led to a significant improvement with retrograde lacrimal duct airflow. However, patient continued to have significant dryness of the eyes despite having normal eyelid closure during sleep. Eye dryness was further improved with patient wearing tanning bed goggles. Patient had improved compliance and resolution of the side effect with the interventions. CONCLUSION: The retrograde lacrimal duct airflow during PAP therapy is a rare complication that has improved substantially with a sequence of interventions. Namely, decreasing PAP pressure settings, total face mask, and tanning bed goggles.